Determinants of Burden of Disease among Rice Farming Households in Ogun State, Nigeria - K. O, Aboaba; T. O, Oyekale; S. A, Adewuyi; S. O, Adigbo (Asian Journal of Agriculture and Rural Development, 2019)
This study was carried out to indicate the factors, which could determine the burden of disease among rice farming households in Ogun state in Nigeria. Multi-stage sampling procedure was used to select 240 rice farming households. The study showed that nearly all households took drugs or medicines without consulting a doctor or pharmacist. Low level of income (85.33%), lack of awareness of health facilities (52.02%), low level of education (58.22%), as well as hindrances in distance and difficult terrains towards health facilities (75.11%) were indicated as the critical problems being faced by the households from using public health facilities. Sex, household size, off-farm income, distance to health care services and dirt floor of home were positively and significantly considered to influence disease burden, while age, cooperative membership, labor used and health conditions had negative effects. The study concluded that increased distance to health care services increased the burden of diseases of the households. It was therefore, recommended that health facilities should be located nearer to the people’s locations to increase its appropriate use. This would gradually improve their health conditions, and thereby reduce the ill-health cost in the long run.